Blin, Kazimir Evgen'evich (helicopter-pilot) and Pavlov, Oleg Leonidovich (helicopter-mechanic)
About air force operations related to cleaning up the consequences of the explosion; ignorance of officers about radiation and uneven effect of radiation on pilots and liquidators; evaluation of the organization of the air force operations.